The Complete Fables of Jean de La Fontaine - La Fontaine, Jean de, 1621-1695 (Book collections on Project MUSE., 2007)
Charming and elegant, Jean de La Fontaine's (1621-1695) animal fables depict sly foxes and scheming cats, vain birds and greedy wolves, all of which subtly express his penetrating insights into French society and the beasts found in all of us. Norman R. Shapiro has been translating La Fontaine's fables for over twenty years, capturing the original works' lively mix of plain and archaic language. This newly complete collection is destined to set the English standard for the oeuvre of one of the world's greatest fabulists.